Augmented materials: spatially embodied sensor networks. (1st January 2013) - Razzaque, M.A.; Dobson, Simon; Delaney, Kieran
Wireless sensor networks are increasingly common in medical, environmental monitoring, precision agriculture, smart home monitoring, and other applications. Most wireless sensor networks operate in air or liquid media: in this paper we are concerned with the design and implementation of sensor networks embedded into solid materials, thus placing sensing and processing capabilities into the fabric of built objects and environments. We introduce the concept and its component challenges, and present some early work demonstrating the feasibility of such 'augmented' materials to provide semantically rich sensing and response.